A 16-year bicentric retrospective analysis of ovarian tissue cryopreservation in pediatric units: indications, results, and outcome - Grellet-Grün, Marine; Delepine, Béatrice; Le Van Quyen, Pauline; Avérous, Gerlinde; Durlach, Anne; Greze, Cécile; Ladureau-Fritsch, Laetitia; Lichtblau, Isabelle; Canepa, Anne-Sophie; Liné, Antoine; Paillard, Catherine; Pluchart, Claire; et al. (Frontiers in Endocrinology, 2023)
Backgrounds: Cancer treatments of last decades improve the survival rate of children and adolescents. However, chemo-and radiotherapy result in gonadal damage leading to acute ovarian failure and sterility. The preservation of fertility is now an integral part of care of children requiring gonadotoxic treatments.OTC is an effective fertility preservation option which allows long-term storage of primordial follicles, subsequent transplantation and restoration of endocrine function and fertility. The efficacy of this technique is well-demonstrated in adults but the data are scarce for pediatric patients.Currently OTC represents the only possibility of preserving the potential fertility in prepubertal girls.between the age of the patients and the number of fragments (p < 0.001). More fragments were obtained from partial bilateral harvesting than from whole ovary harvesting (p < 0.05). Histological analysis of ovarian tissue showed a median of 6.0 primordial follicles/mm2 [0.0-106.5] and no malignant cells were identified. A negative correlation was found between age and follicular density (p < 0.001). Median post-harvest follow-up was 92 months . 15 girls had died, 11 were still under treatment for their pathology and 46 were in complete remission. Of all patients, 29 (40.2%) were subjected to a hormonal status evaluation and 26 were diagnosed with premature ovarian insufficiency (POI) (p < 0.001). One patient had undergone thawed ovarian tissue transplantation.OTC should be proposed to all girls with high risk of developing premature ovarian insufficiency following gonadotoxic therapies in order to give them the possibility of fertility and endocrine restoration.